Fostering nursing innovation to prevent and control antimicrobial resistance using approaches from the arts and humanities. (May 2020) - Macduff, Colin; Marie Rafferty, Anne; Prendiville, Alison; Currie, Kay; Castro-Sanchez, Enrique; King, Caroline; Carvalho, Fernando; Iedema, Rick
Background: Efforts to address the complex global problem of antimicrobial resistance (AMR) highlight the need for imagination and innovation. However, nursing has not yet leveraged its potential to innovate to prevent AMR advancing. Aims: This paper focuses on the initial phase of an ongoing research and development study that seeks to foster nursing imagination and innovation by enhancing the meaningfulness of AMR for practising nurses and by facilitating their creative ideas. Methods: This aim is addressed through application of arts and humanities approaches, in particular the use of visualisation, co-design and historical methods, underpinned by the Design Council Double Diamond process model. The first phase with 20 UK participants explored how hospital and community-based nurses understand and respond to the priorities and consequences of AMR within their everyday working lives. Results: Nurses varied in their conceptualisations of AMR and in their depictions and explanations of its meaning and priority within everyday practices. Some saw infection prevention and control as bound up with AMR, whereas others differentiated in the context of specific work activities. Insights into related reasoning and practice tactics were also generated. Conclusions: The initial project phase provides a basis for fostering nursing innovation in this important field.